China-South Pacific Relations: China’s Approach in China-Pacific Island Countries Economic Development and Cooperation Forum - Yohanes Ivan Adi Kristianto; Muhammad Fachrie; Wijoseno Cahyo Atmojo; Ahmad Rif’an (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
People's Republic of China or commonly known as China has been transformed as one of the respected rising powers. China's hegemony in various regions is strongly supported by its economic power and military strength. The strength of these two aspects has influenced China's growing political power in international politics. In the economic aspect, China strengthens its influence by establishing economic cooperation relations with various international entities, including the Pacific Island countries. One form of such cooperation is the China-Pacific Island Countries Economic Development and Cooperation Forum. This research aims to answer the question of why China is attempting to intensify economic cooperation with Pacific Island countries. The authors decided to focus on the research with time scope 2011-2019 because China began to intensify the cooperation since 2011. Meanwhile, China's offer of financial assistance was last identified in 2019, so that year is selected to be the limit for the research focus. Furthermore, the conceptual framework utilized is regime formation and regional hegemon. We argue that the cooperation undergone by China in South Pacific is to establish an economic cooperation regime. By establishing the regime, China intends to become a hegemon in South Pacific, at once decrease the influence of the United States and Australia in that region and secure its political interest in Southeast Asia where this territorial has become a power struggle field between China and the United States.